Cycle length and COD/N ratio determine properties of aerobic granules treating high-nitrogen wastewater - Cydzik-Kwiatkowska, Agnieszka (Springer Berlin Heidelberg, 2013)
Aerobic granule characteristic in sequencing batch reactors treating high-nitrogen digester supernatant was investigated at cycle lengths (t) of 6, 8 and 12 h with the COD/N ratios in the influent of 4.5 and 2.3. The biomass production (Y (obs)) correlated with the extracellular polymeric substances (EPS) in grams per COD removed. Denitrification efficiency significantly decreased as the amount of EPS in biomass increased, suggesting that organic assimilation in EPS hampers nitrogen removal. Granule hydrophobicity was highest at t of 8 h; the t has to be long enough to remove pollutants, but not so long that excessive biomass starvation causes extracellular protein consumption that decreases hydrophobicity. At a given t, reducing the COD/N ratio improved hydrophobicity that stimulates cell aggregation. At t of 6 h and the COD/N ratio of 2.3, the dominance of 0.5–1.0 mm granules favored simultaneous nitrification and denitrification and resulted in the highest nitrogen removal. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00449-013-1102-4) contains supplementary material, which is available to authorized users.